2011
DOI: 10.4236/ajps.2011.23056
|View full text |Cite
|
Sign up to set email alerts
|

Purified Wheat Gliadin Proteins as Immunoglobulin E Binding Factors in Wheat Mediated Allergies

Abstract: Some wheat gliadin proteins are strong allergens that may cause various symptoms of food allergies and baker’s asthma. The most immunoreactive ω-5 gliadin fractions are the main allergens in wheat dependent exercise induced anaphylaxis (WDEIA). While the allergenicity of ω-5 is quite well understood, knowledge about α, β, γ and ω-1.2 gliadins is much more scanty. This study examines allergenic properties of other fractions as compared to ω-5. Gliadins were extracted from flour of winter wheat (Triticum aestivu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…The analyzed wheat hybrids were immuno-positive for a number of bands representing α, β, γ gliadins, LMW glutenins and NGP. These results have confirmed the immunoreactivity of α, β and γ gliadins, previously reported in our study that tested purified gliadin fractions by ELISA [28]. The current work is also consistent with the results obtained by other authors who reported allergenicity of α, β and γ gliadins in atopic dermatitis, and LMW glutenins in baker's asthma [20,29,30].…”
Section: Discussionsupporting
confidence: 82%
“…The analyzed wheat hybrids were immuno-positive for a number of bands representing α, β, γ gliadins, LMW glutenins and NGP. These results have confirmed the immunoreactivity of α, β and γ gliadins, previously reported in our study that tested purified gliadin fractions by ELISA [28]. The current work is also consistent with the results obtained by other authors who reported allergenicity of α, β and γ gliadins in atopic dermatitis, and LMW glutenins in baker's asthma [20,29,30].…”
Section: Discussionsupporting
confidence: 82%
“…The highest decrease of immunoreactivity was observed in GDL lacking the ω-5 gliadin band confirming the highest allergenicity and immunodominant character of ω gliadins in allergies to wheat, especially ω-5 fractions that may trigger WDEIA [21,22]. However, decrease of IgE binding with GDL of reduced number of β fractions confirms our previous results on immunoreactivity of individual, purified gliadins indicating that other gliadin groups (besides the ω gliadins) may also share allergenicity of the protein complex [23].…”
Section: Discussionsupporting
confidence: 74%
“…Sixty aliquots of 7 ml containing gliadin fractions were collected beginning 5 h after the start of electrophoresis using pH 3.1 aluminum lactate buffer as eluent. The separation was completed 12 h after the onset of fraction collection (Bernardin et al 1967;Waga & Zientarski 2007;Waga et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…They are one of the most complex and polymorphic protein groups in the plant kingdom. Gliadins of a single wheat genotype are composed of hundreds of polypeptides controlled by six complex loci on chromosomes belonging to the 1 st and 6 th homology groups (1A, 1B, 1D, 6A, 6B, and 6D) of the hexaploid wheat genome (Triticum aestivum L.) (Payne 1987;Waga et al 2011). Particular loci comprise from several to several hundred closely linked genes which are inherited as clusters.…”
mentioning
confidence: 99%
See 1 more Smart Citation